1999
DOI: 10.1002/1531-8249(199901)45:1<82::aid-art14>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Increased activity of surviving locus ceruleus neurons in Alzheimer's disease

Abstract: In Alzheimer's disease (AD) there is neuronal loss in the locus ceruleus (LC), and the noradrenergic system may be even more affected in depressed AD patients. However, this neuronal loss may go together with an increase in activity of the remaining noradrenergic neurons. We prospectively evaluated 16 AD patients (6 depressed, 5 transiently depressed, and 5 nondepressed) and 10 controls. We determined norepinephrine and its metabolite 3‐methoxy‐4‐hydroxyphenylglycol (MHPG) in various brain areas, and compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
101
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(110 citation statements)
references
References 52 publications
8
101
1
Order By: Relevance
“…Importantly, the loss of LC neurons was found to be more extensive and to correlate better with the progression of AD than the cholinergic cell loss observed in the nucleus basalis of Meynert (15,16). In contrast, compensatory mechanisms regarding NE levels in the CSF and the mRNA expression of α2-adrenoreceptors in the hippocampus of AD patients have been suggested (17)(18)(19). However, it is unclear whether increased NE measured form the CSF is congruent with the NE secreted from LC projection areas, but being produced in the brainstem or by terminally degenerated LC neurons.…”
Section: Ne Depletion Decreases Microglial Phagocytosis and Recruitmementioning
confidence: 96%
See 1 more Smart Citation
“…Importantly, the loss of LC neurons was found to be more extensive and to correlate better with the progression of AD than the cholinergic cell loss observed in the nucleus basalis of Meynert (15,16). In contrast, compensatory mechanisms regarding NE levels in the CSF and the mRNA expression of α2-adrenoreceptors in the hippocampus of AD patients have been suggested (17)(18)(19). However, it is unclear whether increased NE measured form the CSF is congruent with the NE secreted from LC projection areas, but being produced in the brainstem or by terminally degenerated LC neurons.…”
Section: Ne Depletion Decreases Microglial Phagocytosis and Recruitmementioning
confidence: 96%
“…Even if remaining LC neurons show an increased activity in an attempt to compensate for the ongoing degeneration (17,19), thereby generating at their terminals locally high NE levels, it seems likely that progressive LC degeneration may consequently cause neuroinflammation and a paralysis of phagocytotic clearance that first affects single spots but later the entire LC projection area. Such a chronic impairment of microglial Aβ clearance may ultimately contribute to the progression of the disease itself.…”
Section: Ne Depletion Decreases Microglial Phagocytosis and Recruitmementioning
confidence: 99%
“…Since the rostral portion of the LC innervates forebrain structures such as the hippocampus, whereas the caudal portion of the LC innervates hindbrain structures such as the cerebellum and spinal cord Loughlin et al, 1982), the rostral-tocaudal distance of the LC was separately analyzed. Sections were systematically analyzed to include the 30, 50, and 70% levels of the LC, considering the rostral part (or 0%) as the beginning of the trochlear nucleus, and the caudal pole (100%) ended at the rostral level of the trigeminal motor nucleus (Hoogendijk et al, 1999). Estimation of the volume (Vref) of LC and SN was performed with the Cavalieri method, and the optical dissector method was used to estimate neuronal density (Nv).…”
Section: Quantification Of Tyrosine Hydroxylase Positive Cellsmentioning
confidence: 99%
“…There is a significant loss of noradrenergic neurons in the LC in AD (Mann et al, 1980;Tomlinson et al, 1981;Bondareff et al, 1982;Marcyniuk et al, 1986;Chan-Palay and Asan, 1989;German et al, 1992). However, the surviving neurons in the LC appear to be compensating for the neuronal loss (Adolfsson et al, 1979;Cross et al, 1981;Mann et al, 1981;Perry et al, 1981;Tomlinson et al, 1981;Gottfries et al, 1983;Raskind et al, 1984;Palmer et al, 1987;Reinikainen et al, 1988;Tohgi et al, 1992;Elrod et al, 1997;Russo-Neustadt et al, 1998;Hoogendijk et al, 1999;Szot et al, 2000). Recently, our laboratory showed that the remaining noradrenergic neurons in the LC of AD and a related dementing disorder, dementia with Lewy bodies (DLB), showed three different compensatory changes: (1) an increase in tyrosine hydroxylase mRNA expression in the remaining neurons; (2) sprouting of dendrites into the peri-LC dendritic zone, as determined by α 2 -adrenoreceptor (AR) and norepinephrine transporter binding sites; and (3) sprouting of axonal projections into the hippocampus as determined by α 2 -ARs (Szot et al, 2006).…”
mentioning
confidence: 99%